A pillar[5]arene-fused cryptand: from orthogonal self-assembly to supramolecular polymer1. Issue 17 (28th February 2015) - Wang, Qi; Cheng, Ming; Zhao, Yue; Wu, Lin; Jiang, Juli; Wang, Leyong; Pan, Yi
<x xml:space="preserve">Abstract</x> A supramolecular polymer based on a novel pillar[5]arene-fused cryptand host was successfully constructed by the orthogonal self-assembly of two host–guest interactions.